Essays on the Peripheries - Valente, Peter (punctum books, 2021)
"Essays on the Peripheries contains essays written by translator and scholar Peter Valente over a twenty-year period, stretching from the 1990s to 2019. They are a record of literary exploration and discovery, concerned with the recovery of lost works, with those writers whose works were out of print or hard to find, and whose names were somehow not fashionable in the current discourse, but who are important nevertheless. Edouard Roditi, Barbara Barg, and Tom Savage, for example, should be better known, but their books are largely ignored. This collection of essays highlights those works on the periphery, such as Turkish poets Seyhan Erözçelik and Küçük İskender, while it also includes several essays on better-known queer authors like Pierre Guyotat and Pier Paolo Pasolini, focusing on often overlooked qualities in their work that bear looking at closely. These essays on works of literature are complemented by a number of texts on jazz, again highlighting important and interesting figures in the world of jazz and free improvisation that may have fallen through the cracks, such as the pianist Richard Twardzick and the Ganelin trio, which recorded their great experimental work Ancora da Capo in 1980, behind the Iron Curtain. Attention is also to given to more popular figures such as Stan Getz. The volume is completed with a series of essays reappraising Roman poets in the twenty-first century, offering fresh new translations and readings of authors such as Catullus and Callimachus. A collection of essays, like an anthology, is by its nature incomplete. Essays on the Peripheries is a kind of sketch, rather than a finished portrait, of the author's changing impressions on various subjects over the years."